Internet Addiction and Sleep Quality Among Medical Students of Delhi: A New Age Epidemic - Nitesh Chauhan; Poornima Tiwari; Pooja Ahlawat; Sunil kumar Singh; Bhushan Dattatray Kamble; Gunjan Mahaur (Medsci Publications, 2022)
Background: Recently there is an explosive growth of internet usage among youth worldwide. Internet addiction is defined as psychological dependence on the Internet leading to inability to control one's use of the Internet. Objective: To study the prevalence of internet addiction and quality of sleep among medical students of Delhi and to find out the factors associated with internet addiction. Methods: A cross-sectional study, using stratified random sampling method was conducted among undergraduate students of VMMC & Safdarjung hospital Delhi. Young's internet addiction test and Pittsburgh sleep quality index was administered. Results: Mean age of study participant was 20.3 ± 2.3 SD years. Internet addiction was found in more than half of the study participant. Poor sleep quality was also found in more than half (57.2%) of them. On analysing internet addiction with associated factors, it was observed that gender, monthly data usage, source of internet use, phone use while eating, ever notice by teacher in class while using phone, monthly expenditure and quality of sleep were statistically significantly (p < .001) associated. Conclusion: This study implies that internet addiction was high among medical student. More than half of the study participants was suffering from poor sleep quality.